The Change in the Power Elements of the USA between 2001 and 2020 and Its Impact on the Structure of the International System - Demet Güntay Uçar; Burak Samih Gülboy (Güvenlik Stratejileri Dergisi)
ower and leadership are a multi-layered and relational process. However, political decision- makers often tend to reduce power to the resources possessed and the results that can be achieved with them. This one-dimensional perspective leads to an understanding of power based on hard power elements such as coercion, control, and domination. When an actor who wants to maintain or increase its power overloads its power elements to establish power and domination over other actors, it can leads to a situation called “power fatigue”. Power fatigue limits the capacity of the dominant actor to generate solutions, leading to crises at both the unit and system levels. In this context, the study aims to analyze the conceptualization of power fatigue through the periods of Bush, Obama, and Trump, considering the dominant role of the United States of America (USA) in the international system shaped after the Cold War.